METHOD FOR PREDICTING VASCULAR AGING, METHOD FOR PREDICTING DISEASE RISK, BIOMARKER FOR PREDICTING VASCULAR AGING, BIOMARKER FOR DISEASES, MEASUREMENT KIT, AND DIAGNOSTIC DEVICE - SHIMIZU Hideo; HONDA Yoshitomo; KAWAMOTO Akiyo; UEDA Mamoru; HAMADA Yoshihiro; NINOMIYA Yuichi; KAWAZOE Takayoshi; TAKAHASHI Kazuya (2021)
Provided are: a biomarker which can be used in the diagnosis of vascular aging in a subject and is included in a biological sample taken from the subject; and a method and a biomarker for not only evaluating the degree of progression of vascular aging in the subject by measuring an expression level of the biomarker but also determining the presence or absence of arteriosclerotic disease, cerebrovascular disease, cardiovascular disease, or other aging-related diseases of the subject. The gene expression level of one or both of CMPK2 and RNF213, which are contained in the biological sample taken from the subject as a biomarker for predicting vascular aging, are measured. In addition, the gene expression level of one or both of CMPK2 and RNF213, which are contained in the biological sample taken from the subject as a biomarker for arteriosclerotic disease, cerebrovascular disease, or cardiovascular disease, are measured. Saliva can be suitably used as a biological sample taken from a subject. L'invention concerne un biomarqueur pouvant être utilisé dans le diagnostic du vieillissement vasculaire chez un sujet et étant inclus dans un échantillon biologique prélevé chez le sujet, et un procédé et un biomarqueur pour non seulement évaluer le degré de progression du vieillissement vasculaire chez le sujet par la mesure d'un niveau d'expression du biomarqueur, mais également pouvoir déterminer la présence ou l'absence d'une maladie liée à l'artériosclérose, d'une maladie cérébrovasculaire, d'une maladie cardiovasculaire, ou d'autres maladies liées au vieillissement du sujet. Le niveau d'expression génique d'un ou des deux parmi CMPK2 et RNF213, étant contenus dans l'échantillon biologique prélevé chez le sujet sont mesurés, en tant que biomarqueur pour prédire le vieillissement vasculaire. De plus, le niveau d'expression génique d'un ou des deux parmi CMPK2 et RNF213, étant contenus dans l'échantillon biologique prélevé chez le sujet sont mesurés, en tant que biomarqueur pour une maladie liée à l'artériosclérose, une maladie cérébrovasculaire ou une maladie cardiovasculaire. La salive peut être utilisée de façon appropriée en tant qu'échantillon biologique prélevé chez un sujet. 被験者における血管老化の診断に利用可能であり、該被験者から採取した生体試料中に含まれるバイオマーカーと、該バイオマーカーの発現レベルを測定することにより、被験者の血管老化の進行の程度を評価するとともに、被験者の動脈硬化性疾患、脳血管疾患、心血管疾患、その他の加齢関連疾患の有無を判定するための方法およびバイオマーカーを提供する。血管老化予測用バイオマーカーとして、被験者から採取した生体試料に含まれる遺伝子ＣＭＰＫ２とＲＮＦ２１３の何れかの遺伝子、または両方の遺伝子の発現レベルを測定する。また、動脈硬化性疾患、脳血管疾患または心血管疾患の疾患用バイオマーカーとして、被験者から採取した生体試料に含まれる遺伝子ＣＭＰＫ２とＲＮＦ２１３の何れかの遺伝子、または両方の遺伝子の発現レベルを測定する。被験者から採取する生体試料として、唾液を好適に用いることができる。